A Diagnostic Conundrum in a Localized Ascending Aortic Aneurysm - Affirul Chairil Ariffin; Hanizah Ngadiron; Firdaus Hayati; Nornazirah Azizan; Fairrul Kadir; Andee Dzulkarnaen Zakaria (2018)
Aortic dissection (AD) is an uncommon life-threatening emergency. Its development is usually subtle and easily missed. On the other hand, an aneurysm nearly always requires immediate surgical intervention. Both interventions are technically different and pose their own challenges. We experienced a distinct case of AD of the ascending aorta in a 65-year-old lady, who presented with a sudden onset of severe chest pain and shortness of breath. Thoracic aortic aneurysm was suspected as computed tomography revealed a saccular aneurysm of the proximal ascending aorta with no involvement of the valve and aortic branches. Surgery was decided after considering the risk of rupture and mortality. However, a diagnosis of localized aortic dissection was discovered and repaired accordingly. We discuss the pitfalls of diagnostic modalities and the techniques of surgical repair.